The caridean shrimps of the genus Lysmata Risso, 1816 (Decapoda: Lysmatidae) from Madagascar collected during the Atimo-Vatae expedition: a new species and two new records - Ashrafi, Hossein; Baeza, J. Antonio; Ďuriš, Zdeněk (European Journal of Taxonomy, 2021)
The present study focuses on shrimps belonging to the genus Lysmata Risso, 1816, collected from Madagascar during the Atimo Vatae expedition carried out in 2010. Lysmata malagasy sp. nov. is a new species belonging to the clade named “long accessory ramous” or “cosmopolitan” in previous phylogenetic studies. The new species can be distinguished from the only two other representatives of this group in the Indo-west Pacific, L. ternatensis De Man, 1902, and L. trisetacea (Heller, 1861), by the accessory ramus of the lateral antennular flagellum consisting of four elongated articles. Lysmata lipkei Okuno & Fiedler, 2010 is reported here from Madagascar with a remarkable extension of its known range after its original description from Japan. This species has also been reported from Singapore and, as alien species, from Brazil. Lastly, L. kuekenthali De Man, 1902 known from numerous localities in the Indo-West Pacific biogeographic area, is reported for the first time from Madagascar. Results of the present morphological and molecular analyses suggest that L. hochi Baeza & Anker, 2008 from the Caribbean Sea is a synonym of the Indo-West Pacific L. kuekenthali, and thus the latter species is alien in the western Atlantic.